Developing a Succession and Transition Plan for Chairs - Frederick S. Wood; Holley Tankersley (Academic Chairpersons Conference Proceedings, 2017)
This session will discuss the process of developing a succession plan and making the transition to chair. The presenters will share their experience in making this transition together twice and provide participants with a checklist for planning their own transitions into and out of the position.
Keywords: Career Planning; Academic Leadership; Faculty Development; New Chairs